In situ synthesis and characterization of fluorinated polybenzobisoxazole/silica‐coated magnetic Fe3O4 nanocomposites exhibiting enhanced electromagnetic wave absorption property. Issue 5 (8th April 2014) - Chen, Yong; Qian, Jun; Zhang, Kan; Liu, Xiaoyun; Zhuang, Qixin; Han, Zhewen
<x xml:space="preserve">Abstract</x> A series of magnetic fluorinated polybenzobisoxazole (6FPBO)/silica‐coated Fe3O4 magnetic nanoparticles composites were synthesized through in‐situ polymerization. The structure and morphology of the obtained nanocomposites were characterized by X‐ray diffraction, transmission electron microscopy, and scanning electronic microscope (SEM). The SEM images indicated that the crosslinking structure is formed in magnetic 6FPBO nanocomposites. The magnetic and electromagnetic properties of magnetic 6FPBO nanocomposites in the 2–18 GHz frequency range were characterized by vibration sample magnetometer and vector network analyzer, respectively. The calculated reflection loss of the as‐prepared magnetic 6FPBO nanocomposites showed that the best microwave absorption reached to −20 dB at 17 GHz with a matching thickness of 3.00 mm. POLYM. COMPOS., 36:884–891, 2015. © 2014 Society of Plastics Engineers